Investigation on Residual Compressive Distribution of High-Strength Steel for Bridges by Base Metal Hammer Impact Peening - Yasuyuki Kurihara; Yoshihiro Sakino; Tomoharu Kato (Applied Mechanics, 2021)
Various peening techniques have been used to improve the fatigue strength of steel structures. Among them, base metal impact hammer peening shows significant improvement in fatigue strength in ordinary steel, but the effect on high-strength steel has not been sufficiently studied. Accordingly, this study applied base material hammer impact peening to test specimens of 780 MPa grade high-strength steel (HT780) and 490 MPa grade ordinary steel (SM490), and the residual stress was measured and simulated. The experimental results clarified that a large compressive residual stress was introduced into the inner part of the plate thickness near the indentation in the high-strength steel, although the range of introduction of residual stress was equivalent in both the ordinary steel and high-strength steel.